Vitamin D and exercise improve VEGF-B production and IGF-1 levels in diabetic rats: insights the role of miR-1 suppression - Fatemeh Mazaheri; Rastegar Hoseini; Ahmad Gharzi (Scientific Reports)
Abstract Background Type 2 Diabetes Mellitus (T2DM) is closely associated with the development of vascular damage in the heart. In this study, the researchers aimed to determine whether Aerobic Training (AT) and Vitamin D supplementation (Vit D) could alleviate heart complications and vascular damage caused by diabetes. The effects of an eight-week AT program and Vit D on the expression of miR-1, IGF-1 genes, and VEGF-B in the cardiomyocytes of rats with T2DM. Methods This study was an experimental investigation. Fifty male Wistar rats were divided into 2 groups Non-Diabetic Obese Control (NC; n = 10), and diabetic (n = 40). The rats were then randomly divided into four groups: AT plus Vit D (AT + Vit D; n-=10), AT (n = 10), Vit D (Vit D; n = 10), and Control Diabetic (C; n = 10). The exercise groups underwent treadmill training for 8 weeks at an aerobic intensity equal to 50–60% of their maximal oxygen uptake (VO2max), which corresponded to a speed of 15–25 m/min at a 0% incline, for 30–60 min per day, 5 days per week. The Vit D and AT + Vit D groups received 5,000 international units (IU) of Vitamin D (combined with sesame oil) per week via a single-dose injection. Data were analyzed using one-way analysis of variance (ANOVA) followed by Tukey’s post-hoc test for multiple comparisons among the groups. Paired data were analyzed using paired t-tests. Results The results showed that BW, BMI, and FI significantly decreased in the AT + Vit D (p = 0.001 for all variables), AT (p = 0.001 for all variables), and Vit D (p = 0.001 for all variables) groups compared to baseline. In contrast, BW, BMI, and FI increased in the C (p = 0.001, p = 0.006, p = 0.020, respectively) and NC (p = 0.001 for all variables) groups. Significant differences were observed between the groups in terms of visceral fat, insulin, glucose, and HOMA-IR (p = 0.001 for all variables). Serum 25-hydroxyvitamin D levels varied significantly among the groups (p = 0.002). The AT + Vit D group showed significantly increased VEGF-B (p = 0.001 for both comparisons), upregulated IGF-1 (p = 0.001 for both comparisons), and downregulated miR-1 (p = 0.001 for both comparisons) compared to the AT and Vit D groups, respectively. Conclusions AT and Vit D increased the expression of IGF-1 and VEGF-B in the heart of T2DM rats while decreasing the expression of miR-1. These effects were more pronounced when AT and Vit D were combined. The study concludes that the combination of AT and Vit D has cardio-protective effects in T2DM rats, counteracting abnormal angiogenesis induced by diabetes. These effects are mediated, at least in part, by the upregulation of IGF-1 and VEGF-B, and the downregulation of miR-1.